HUBUNGAN RELIGIUSITAS DAN REGULASI EMOSI SISWA SEKOLAH DASAR - Angelia, Mikha; Tiatri, Sri; Heng, Pamela Hendra (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2020)
Emotional regulation is an individual’s ability to regulate emotions. Individual regulate his/her emotion to be able to control his/her life. In practice, the ability of emotional regulation can be influenced by various factors. One of the factors that can influence the process of emotional regulation is the level of religiosity. In this study, researchers aimed to be able to see the relationship of students’ religiosity on emotional regelation possessed by students. This study involved 319 elementary school students in SD X. Participants were given a set of assessments to measure the level of religiosity and emotional regulation. Religiosity is measured by using the Dimension Religiosity Scale to measure preoccupation, conviction, emotional involvement, and guidance. To measure emotional regulation, researchers used the Emotion Regulation Questionnaire for Children and Adolescent (ERQ-CA) to measure the level of cognitive reappraisal and expressive suppression possessed by students. Data was analysised using correlation test  in SPSS version 23. From the results of the correlation test conducted found that there is a significant relationship between the variables of religiosity and emotional regulation (r = 0.248, with p < 0.05). This shows that if the level of religiosity students have is high, the ability of students to regulate emotions will be better. Regulasi emosi adalah suatu kemampuan individu dalam mengatur emosi. Setiap orang melakukan regulasi emosi untuk dapat mengendalikan hidupnya. Dalam praktiknya, kemampuan regulasi emosi dapat dipengaruhi oleh berbagai faktor. Salah satu faktor yang dapat mempengaruhi proses regulasi emosi adalah tingkat religiusitas yang dimiliki individu tersebut. Dalam penelitian ini, peneliti bertujuan mengkaji hubungan antara religiusitas siswa dengan regulasi emosi yang dimiliki oleh siswa. Penelitian ini melibatkan 319 siswa-siswi Sekolah Dasar di sekolah X. Partisipan diberikan satu set asesmen untuk mengukur tingkat religiusitas dan regulasi emosi. Religiusitas diukur dengan menggunakan Dimension Religiousity Scale untuk mengukur preoccupation, conviction, emotional involvement, dan guidance. Untuk mengukur regulasi emosi, peneliti menggunakan Emotion Regulation Questionnaire for Children and Adolescent (ERQ-CA) untuk mengukur tingkat kemampuan cognitive reappraisal dan expressive suppression yang dimiliki oleh siswa. Analisis data menggunakan uji korelasi dengan menggunakan SPSS versi 23. Dari hasil uji korelasi yang dilakukan, didapatkan bahwa ada hubungan yang signifikan antara variabe religiusitas dan regulasi emosi (r = 0,248, p < 0,05). Hal ini menunjukkan bahwa makin tinggi tingkat religiusitas yang dimiliki siswa, maka makin tinggi pula kemampuan siswa dalam meregulasi emosi.